Geographical, botanical and chemical profile of monofloral Italian honeys as food quality guarantee and territory brand. (4th May 2017) - Di Marco, G.; Manfredini, A.; Leonardi, D.; Canuti, L.; Impei, S.; Gismondi, A.; Canini, A.
Abstract: Bees represent an important element for the preservation of plant biodiversity. During their activities, bees cover a large area around the hive and their products strictly reflect the distinctive traits of these environments. In honey, the floral diversity of the areas inspected by bees is revealed by their pollen spectra. The present work characterized 460 Italian unifloral honeys by melissopalynological and physicochemical analyses. Obtained data contributed to: confirm the botanical identity of the samples; determine the plant biodiversity revealed in each honey; differentiate the samples of the same monofloral typology in relation to their geographical origin; and identify peculiar floristic associations in the Italian regions. Moreover, gas chromatographic analysis was carried out on rare unifloral honey to study their sugar profiles. This work provided the scientific base to create a valid tool able to assign a territorial brand and an authenticity guarantee to the honey, protecting the consumers from adulterations.